Effects of deacetylation degree, molecular weight, and preparation method on wet‐adhesive and rheological properties of chitosan as food‐grade adhesive. Issue 8 (3rd June 2022) - Guo, Yunsi; Liu, Wenfeng; Dong, Shiliang; Li, Yingxue; He, Jiewang; Liu, Fengfeng; Li, Ran; Zhang, Suyun; Cai, Lei; Zhang, Yue
Abstract: In this study, the impacts of deacetylation degree and molecular weight on the rheological and adhesive properties of chitosan (CS) including shear viscosity, initial viscosity, and peel strength of tobacco leaves have been studied. The effect of different dissolution solvents such as acetic acid (HAC) and lactic acid (HL) on chitosan adhesives was also investigated. The results revealed that the adhesive properties increased first and then decreased with the increase of deacetylation degree, while chitosan with higher molecular weight showed higher initial adhesiveness and peel strength values. Chitosan sample III with a medium deacetylation degree of 80.5% showed the best adhesion properties with an excellent ability to reduce the total mold and yeast on the surface of tobacco leaves. Sample HL‐CS‐III showed a lower initial adhesiveness value but a higher peel strength value than sample HAC‐CS‐III due to its more viscous nature. Overall, chitosan showed great potential to be used as adhesives for cigar wrapping and other food applications. Novelty impact statement: The adhesive properties of chitosan molecules with different molecular weights and degrees of deacetylation values are compared. Chitosan with a larger molecular weight and medium deacetylation degree shows maximum initial adhesiveness and peel strength to tobacco leaf. Chitosan dissolved in lactic acid had a higher peel strength value and better mechanical resistance than acetic acid‐dissolved chitosan adhesive.